MRSA carrying mecC in captive mara. (25th February 2015) - Espinosa-Gongora, C.; Harrison, E. M.; Moodley, A.; Guardabassi, L.; Holmes, M. A.
Abstract: Objectives: To characterize the staphylococcal cassette chromosome mec (SCC mec ), virulence and antimicrobial susceptibility of Staphylococcus aureus ST130 isolated from mara ( Dolichotis patagonum ), a large rodent species native to South America and kept in captivity at Copenhagen Zoo. Methods: The presence of mecC was confirmed by PCR in 15 S. aureus ST130 isolated from mara during a previous study. WGS was performed on two randomly selected isolates to characterize their genomes with respect to SCC mec, virulence and resistance gene content. Antimicrobial susceptibility was tested using commercial broth microdilution tests. Results: All the isolates belonged to spa type t528 ST130 and carried mecC . Based on WGS, mecC was 100% identical to the prototype sequence of S. aureus strain LGA251. The sequence of SCC mec type XI in the mara isolates had 23 SNPs compared with the one described in LGA251. The two sequenced strains harboured a set of virulence factors and other genomic features previously observed in ST130. Both strains carried norA as the only putative antimicrobial resistance gene in addition to mecC . Conclusions: Our findings support the notion that a genetically conserved mecC -carrying MRSA ST130 clone is widespread in a variety of unrelated hosts in Denmark. Since the mara at Copenhagen Zoo have limited contact with humans and other animal species, it remains unclear whether mara are natural hosts of ST130 or acquired this lineage from unknown sources. The broad host range of MRSA ST130 supports its designation as a generalist lineage.